Arta Musaraj and I, and the Wonderful Idea of the “New Academy” Born in Her Homeland, Albania - In memoriam of Arta Musaraj (August 28, 1974 – May 18, 2025) - Guglielmo Chiodi (Academicus International Scientific Journal)

(untitled)
On May 18, 2025, Prof Arta Musaraj, founder and editor-in-chief of Academicus International Scientific Journal, passed away after a long battle with cancer at 50 years-old. Arta Musaraj has returned to her home, to God. The scientific journal Academicus ISJ founded and directed by her, a window always open for science, will challenge the times forever.